2020
DOI: 10.18632/aging.102819
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of long non-coding RNA H19 in glioma via integrated bioinformatics analyses

Abstract: Numerous discoveries have elucidated that long noncoding RNAs (lncRNAs) play a critical role in cancer malignant progression. However, their potential involvement in gliomas remains to be explored. Herein, the expression level of lncRNA H19 in glioma tissues, and its relevance with clinical characteristics were analyzed through Oncomine. The results showed that H19 was highly expressed in glioma tissues and its expression increased with the increase of malignancy. Next, GTEx and TCGA data were downloaded for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
(46 reference statements)
1
39
0
Order By: Relevance
“…Studies by Deng et al showed that prognostic models based on immune-related genes have been developed and proved to have good predictive performance, which provided theoretical ideas for the immunotherapy of LGG (20). Studies show that many lncNRAs had important effects on the immune microenvironment of gliomas (12), for example, lncRNA H19 could affect the level of immune infiltration of gliomas, as a result of affecting the prognosis of patients (21). In view of the important role of immune-related lncRNAs, Shen et al applied ssGSEA to identify immune-related lncRNAs associated with the prognosis of breast cancer, and constructed a risk scoring model to predict the OS of patients with breast cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Deng et al showed that prognostic models based on immune-related genes have been developed and proved to have good predictive performance, which provided theoretical ideas for the immunotherapy of LGG (20). Studies show that many lncNRAs had important effects on the immune microenvironment of gliomas (12), for example, lncRNA H19 could affect the level of immune infiltration of gliomas, as a result of affecting the prognosis of patients (21). In view of the important role of immune-related lncRNAs, Shen et al applied ssGSEA to identify immune-related lncRNAs associated with the prognosis of breast cancer, and constructed a risk scoring model to predict the OS of patients with breast cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…GSEA analysis was carried out as previously reported[ 22 ] to evaluate whether a significant set of genes are associated with the APEX2 difference in LIHC. The GO Ontology was selected as the gene sets database to confirm the cellular component and biological process.…”
Section: Methodsmentioning
confidence: 99%
“…Original gene expression data were measured as fragments per kilobase of transcript per million mapped reads (FPKM) and log2-transformed. Furthermore, the RNA expression profiles were normalized with the R package “sva” to remove batch effects, as previously reported ( Xiao et al, 2020 ; Zhang et al, 2020b ). Then, the “limma” package in R was applied, and genes with an average count value lower than 1 were all excluded from further analyses.…”
Section: Methodsmentioning
confidence: 99%